34 Geriatricians in Intermediate Care Settings: A Modern Approach to Geriatric Medicine. (6th February 2020) - Enwere, P; Mahmood, R; Aranda-Martinez, A; Manzoor, A; Wilkinson, E; Soliman, K; Yeong, K; Lawn, L; Lisk, R
Abstract: Introduction: Due to growing older population with increasing medical complexity and care needs, over-reliance on acute hospitals for care delivery, disconnect between social and medicalised care and challenging national health services (NHS) financial climate, it is essential to provide much of this care to our older patients outside the acute hospital before they reach crisis point. This prevents unnecessary hospital admissions and outpatient referrals especially to our geriatric services. Therefore, newer and innovative care models are required to cater the needs of our aging population especially within the community settings. The North West Surrey clinical commissioning group (CCG) catchment area is divided into three localities, namely SASSE Locality in Spelthorne, Thames Medical Locality in Runnymede/West Elmbridge, and the Woking Locality (Bedser hub) in Woking. Locality hub model of integrated care led by GP with multidisciplinary (MDT) input along with wellbeing coordinators was introduced to address above issue. Objectives: Our mission was to find a way to manage the challenges we face from a growing older population within an integrated GP-led community service and in a manner that promotes independence, reduce social isolation, improve patient experience and safely deliver appropriate acute care in the community whilst reducing dependency on regional acute hospitals. A fully qualified geriatrician input was introduced within the hub model at Bedser hub. Results: Total savings: £16, 484, Geriatricians input cost: £16, 500 Cost neutral intervention Conclusions: Newer models of collaborative healthcare within the community dwellings with GP and geriatrician input along with multidisciplinary approach are essential to deliver safe and high quality care to our older population, thus reducing reliance on our ever so stretched local acute NHS hospitals. Our intervention has resulted in reduction of referrals to geriatric outpatient clinic and enabled us to provide the required care to our older population closer to home. It has also led GPs to build their skills in managing the very frail patients with complex needs safely and effectively. In the long run, the intervention will be cost effective with further projected reduction in referrals.